Political science a primer - Islam, Syed Serajul; Moten, A. Rashid (2005)
This book is intended to introduce students to the study of politics, and make them aware of their civil rights and responsibilities as responsible citizens. It also examines 14 issues of importance and concludes with a chapter on the various dimensions of the government and politics in Malaysia.